Tailored functionalization of iron oxide nanoparticles for MRI, drug delivery, magnetic separation and immobilization of biosubstances - Hola, Katerina; Markova, Zdenka; Zoppellaro, Giorgio; Tucek, Jiri; Zboril, Radek (Biotechnology advances, 2015)
In this critical review, we outline various covalent and non-covalent approaches for the functionalization of iron oxide nanoparticles (IONPs). Tuning the surface chemistry and design of magnetic nanoparticles are described in relation to their applicability in advanced medical technologies and biotechnologies including magnetic resonance imaging (MRI) contrast agents, targeted drug delivery, magnetic separations and immobilizations of proteins, enzymes, antibodies, targeting agents and other biosubstances. We review synthetic strategies for the controlled preparation of IONPs modified with frequently used functional groups including amine, carboxyl and hydroxyl groups as well as the preparation of IONPs functionalized with other species, e.g., epoxy, thiol, alkane, azide, and alkyne groups. Three main coupling strategies for linking IONPs with active agents are presented: (i) chemical modification of amine groups on the surface of IONPs, (ii) chemical modification of bioactive substances (e.g. with fluorescent dyes), and (iii) the activation of carboxyl groups mainly for enzyme immobilization. Applications for drug delivery using click chemistry linking or biodegradable bonds are compared to non-covalent methods based on polymer modified condensed magnetic nanoclusters. Among many challenges, we highlight the specific surface engineering allowing both therapeutic and diagnostic applications (theranostics) of IONPs and magnetic/metallic hybrid nanostructures possessing a huge potential in biocatalysis, green chemistry, magnetic bioseparations and bioimaging.
Keywords: Magnetic Resonance Imaging; Water treatment; Hyperthermia; Nanoparticles; magnetická rezonanční tomografie; Antibacterial; SERS; Magnetics; magnetismus; Nanoengineering; Drug Delivery Systems; Biotechnology; biotechnologie; Ferric Compounds; Magnetic resonance imaging; lékové transportní systémy; Magnetic separation; nanočástice; železité sloučeniny; Surface design; Biomedical applications